Helicobacter pylori eradication causes perturbation of the human gut microbiome in young adults - Yap T.W.-C.; Gan H.-M.; Lee Y.-P.; Leow A.H.-R.; Azmi A.N.; Francois F.; Perez-Perez G.I.; Loke M.-F.; Goh K.-L.; Vadivelu J. (Public Library of Science, 2024)
Indexed by WOS/SCOPUS